Unraveling the Origins and Development of the Galactic Disk through Metal-Poor Stars - Maria Rah; Manolya Yatman; Ali Taani; Ahmad A. Abushattal; Mohammad K. Mardini
The Milky Way is a spiral galaxy comprising three main components: the Bulge, the Disk, and the Halo. Of particular interest is the Galactic disk, which holds a significant portion of the baryonic matter angular momentum and harbors at least two primary stellar populations: the thin and thick disks. Understanding the formation and evolution of the Galactic disk is crucial for comprehending the origins and development of our Galaxy. Stellar archaeology offers a means to probe the disk’s evolution by listening to the cosmological narratives of its oldest and most pristine stars, specifically the metal-poor stars. In this study, we employed accurate photometric metallicity estimates and Gaia Early Data Release 3 astrometry to curate a pure sample of the oldest Galactic stars. This proceeding presents a summary of our primary findings.
Keywords: Galaxy